Generalized distributed state space model of a CSP plant for simulation and control applications: Single-phase flow validation. (June 2020) - Americano da Costa, Marcus V.; Narasimhan, Arunkumar; Guillen, Diego; Joseph, Babu; Goswami, D. Yogi
Abstract: Concentrating solar thermal power plants, also known as CSP plants, can be of different configurations depending on type of collectors, temperatures, heat transfer fluid, working fluid, and the thermodynamic cycle used in the plant. This leads to complex behavior with nonlinear dynamics, potential instability and parameters that vary in both space and time. In this work, a distributed state space model is proposed to ensure computational flexibility and facilitate industrial applications, such as optimization, control and automation. The format used allows the model to represent the thermal dynamics at different operation points including phase changes (liquid or gas) along the spatial dimension. To validate the model, some experimental tests have been made on an operating solar thermal plant located at the University of South Florida, in United States, where real input disturbances were applied to compare measurements with model predictions. Preliminary results show good agreement with experimental observations. Literature data of water and steam properties were used in the model, that can be easily extended to direct steam generation (DSG) plants. Highlights: A nonlinear dynamic model is developed in a matrix structure. The algorithms are able to represent phase changes along the space and time. Complex characteristics of the process were considered in the simulations. A real plant of solar energy was operated. The experiments were performed in different weather conditions.